Indole-, imidazole-, and phenyl-alkylamines in the skin of thirteen Leptodactylus species - Erspamer, V. (1964)
The skin of thirteen Leptodactylus species and sub-species has been examined in regard to its content in biogenic amines. This tissue presents, especially in Leptodactylus pentadactylus labyrinthicus and some other species, an unusually rich miscellany of amines, including at least two indolealkylamines (5-hydroxytryptamine and bufotenidine), three hydroxyphenylalkylamines (p-tyramine, candicine, leptodactyline) and five imidazolealkylamines (histamine, N-methylhistamine, N,N-dimethylhistamine, spinaceamine and 6-methylspinaceamine). It is concluded that the Leptodactylus skin must possess aromatic acid decarboxylase activity, tryptophan-5-hydroxylase activity and N-methyltransferase activity. The skin of nearly every Leptodactylus species and sub-species is characterized by a particular spectrum of amines, which evidently may help in systematies of these species.